The Effect of Acute Allergic Reactions on Diastolic Heart Function - Kaya, Oguz Kaan; Dagli, Necati; Yildiz, Mustafa; Karaca, Ilgin; Ustundag, Bilal; Kuzu, Zulfiye; Dogdu, Orhan (Canadian Soc Clinical Investigation, 2014)
Purpose: Diastolic heart failure is characterized by the presence of heart failure symptoms despite preserved systolic function. Cytokines released during allergic reactions may impair diastolic heart function, either through their direct toxic effects or by inducing coronary artery spasm. The purpose of this study was to examine the effects of acute allergic reactions on diastolic heart function. Methods: Fifty patients, randomly selected from those who were admitted to the emergency room between May 2010 and December 2010 with the complaints of rash and itching, and who were subsequently diagnosed with allergic reactions based on the clinical and laboratory findings, were included in the study as the allergy group. Thirty healthy volunteers, in whom the diagnosis of allergy was ruled out based on the clinical and laboratory data, were use as the control group. Diastolic heart functions were evaluated in patients presenting with allergic reaction as well as in control subjects. Results: There was no significant difference between the two groups in terms of basal systolic functions, diameters of the cavities and wall thicknesses, and biochemical parameters. Color M mode flow progression velocities, E ratios, E/A ratios and mitral lateral annulus tissue Doppler velocities measured by echocardiography at Day 0 and Day 5 were significantly altered in the allergy group (p<0.05). Conclusion: Impairment in diastolic functions was observed following acute allergic reactions. Acute allergic reactions could be a cause of mortality and morbidity if they lead to the development of diastolic heart failure.
Keywords: Angina